Albania and China: A Historical Observation of the World Press - The Beginnig of The’70s in 20th Century - Sallata, Ilir (European Journal of Multidisciplinary Studies, 2022)
The Cold War years presented a variety of dynamics not only in the relationships between the two fronts, but even in the relationships within the socialist front. Albania rolled in close alliances from Yugoslavia, Soviet Union to China. This paper focuses on the beginning of the ‘70s in the 20th century, on the “fraternal” Albanian-Chinese relationship seen from the political, social and economical aspects. This period would be the beginning of the cold era of the “ love” between two countries, and the foreign press would have in observation this relationship, where mainly the left oriented newspapers and magazines and not only presented very interesting articles. From this perspective, the Albanian-Chinese relationship was presented in the Austrian, Italian, French, Turkish, West German, American, Hungarian, Polish, Romanian, Soviet, East German, Chinese press. The pages of these newspapers and magazines reflected the great support that China had accorded to Albania, the industrial developments which the latest one had realised thanks to this support. It is noted the presence of the Chinese human resources in Albania and the social influence, the Albanian diplomatic war for the acceptance of China in the United Nation Organisation etc. Some objective articles, chronicles and reportages were continuously evaluating some truths on the beginnings of divergencies between Tirana and Bejing. Associating the China approach to USA with the Albanian scepticism, the Albanian discontent started to come to light in this aspect. In the press of the time, the Albanian-Chinese relationship started to be reflected as a friendly correct relationship, in the social and economic plan, but with some discrepancies in the ideological plan.